Moderating effect of ownership concentration on the relationship between ceo, audit partner characteristics and real earnings management in Jordan - Alhmood, Mohammad Abed Alrahman (2021)
Earnings management has become a major issue in many global corporate scandals. It can be interpreted as an action purposely conducted by managers of companies to report the accounting earnings which are not in line with the economic reality of the firms for opportunistic or informative purposes. Opportunistic earnings management can cause the quality of published earnings to deteriorate, while also diminishing the trust that investors have in the financial reports. This study investigated the relationship between the characteristics of the Chief Executive Officer (CEO) and the audit partners in relation to real earnings management (REM) in Jordan. Furthermore, the study investigated the moderating role of ownership concentration on the relationship between CEOs, audit partner characteristics and real earnings management. The sample of the study was 348 firm-year observations on firms listed on the Amman Stock Exchange from 2013 to 2018. To test the hypotheses of the current study, multiple regression analysis using STATA software was employed. The results of this study revealed that a CEO’s experience and a CEO’s political connections are positively related to REM. In contrast, CEO duality is negatively associated with REM. Regarding audit partner characteristics it was found that audit partner tenure is related positively with REM, while audit partner affiliation is negatively related to REM. Upon further analysis, the results showed that ownership concentration negatively moderated the relationships between CEO experience and CEO tenure with REM. The findings have implications on investors, regulators and market participants by affording a considerable indication that the characteristics of CEOs, the characteristics of audit partners and ownership concentration are very crucial in explaining REM activities.